Alcohol consumption: risk factors and effects to college students - Patricia Ysabelle S. Dominguez. 4 0 16; 5 (2017)
ABSTRACT: Alcohol consumption among college students has become an integral part of their college lives. With the increasing number of youths engaging in alcohol consumption nowadays, this researcher wanted to know the extent of alcohol consumption among college students and determine its risk factors and effects. Utilizing a descriptive research in order to gain an understanding of underlying reasons for the results of this study, the researcher administered an interview among 12 participants who scored positive on the Alcohol Use Disorder Identification Test (AUDIT) screening. There were 7 males and 5 females in this study. Using descriptive statistics to provide an organized report of the result of the study, it revealed that stress is among the top risk factors of alcohol consumption followed by interaction, reinforcement, emotional and satisfaction. Students drink to socialize, reward themselves, satisfy them and depending on their current mood. Effects of alcohol consumption were mostly negative in family relationships, academic, health and personal. There are also a few positive effects in academic and personal and mostly positive in social relationships which the respondents see as a way to strengthen their relationship.
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2